Cultivo de anteras alternativa biotecnológica útil para la obtención de plantas doble haploide en especies vegetales - Morocho Ochog, Ricardo Alexander (2021)
Anther culture is a very useful biotechnological alternative to generate homozygous plants quickly. Consists of the collection of pollen to induce the formation of vegetative cells, this is due to the capacity of the immature microspores to form a new plant, in the moment incubated in vitro culture, the microspore can generate callus or pass directly to an embryo, depending on the species. Rice panicles are harvested 67 days after cultivation, in this period they contain microspores in uninucleated state, the tillers must be sterilized with ethanol, then passed into the laminar flow chamber, then placed in a glass jar with distilled water, the panicles are separated from the anthers, placed in culture medium and left in a dark room with a temperature of 24 ºC for 34 days, one of the best solutions for the culture medium is: 2mg/L of 2.4-D, 10 mg/L of AFA, 0.5 mg/L of Cinetine, 80g/L of maltose and with a pH of 5.8. For callus regeneration a solution of: 1 mg/L of ANA, 4 mg/L of cinetine, 30 g/L of sucrose, 3 g/L Gellan Gum with an ideal pH of 5.8 is used, then they pass to the acclimatization medium where the roots and undifferentiated leaves , finally they are kept in greenhouse. Tobacco growing does not go through the callus stage, flowers should be collected when the length of the sepals is equal to the petals, each flower is disinfected and transferred to the laboratory where pollen is collected with brushes to be deposited in Petri dishes where they are stored at a temperature of approximately 4ºC, in the multiplication phase one of the most effective regulators is: 0.5 - 1 mL.L-1 of 6-BAP or 1 - naphthalenacetic acid (ANA). Petri dishes containing pollen grains should be covered and incubated in darkness for 20 days at 27 ºC, then passed to light to be grown in tubes with basic growth medium. There are some mitotic inhibitors to perform chromosome duplication among them are colchicine, which has some negative health effects because it is a toxic alkaloid, and orizaline, both with good effectiveness.